Borderline personality traits in attractive women and wealthy low attractive men are relatively favoured by the opposite sex. (1st February 2021) - Blanchard, Alyson E; Dunn, Thomas J; Sumich, Alex
Abstract: Men and women reliably differ on the importance of certain criteria when considering romantic relationships. From an evolutionary perspective that explains sex differences in mating effort and parental investment, men should prioritise attractiveness and women, wealth. Personality traits also signal important information about relationship potential with those of the dark triad facilitating short-term relationships. However, how the vulnerable dark triad traits of borderline personality disorder (BPD) and secondary psychopathyfunction in relationships remains relatively unexplored. Even though interpersonally tempestuous, individuals high in these traits might be alluring in that they offer a thrilling relationship for the short-term, so long as they are also physically appealing. Across two studies, we examined sex differences in partner preference judged on attractiveness in relation to BPD and secondary psychopathy across short- and long-term relationship contexts. Men were willing to engage in relationships with attractive women high in BPD traits, while women compensated low attractiveness for wealth in long-term dating, and did not desire secondary psychopathy in any relationship. Results show that women are more astute in mate preference, avoiding troublesome or financially challenged men who are time and economically costly, and men more readily engage in potentially turbulent relationships.